2021
DOI: 10.3390/cancers13163972
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Based Protein Signatures Associated with Small Cell Lung Cancer

Abstract: Small-cell-lung cancer (SCLC) is associated with overexpression of oncogenes including Myc family genes and YAP1 and inactivation of tumor suppressor genes. We performed in-depth proteomic profiling of plasmas collected from 15 individuals with newly diagnosed early stage SCLC and from 15 individuals before the diagnosis of SCLC and compared findings with plasma proteomic profiles of 30 matched controls to determine the occurrence of signatures that reflect disease pathogenesis. A total of 272 proteins were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…At the same time, Kang et al reported an upregulation of the beta subunit (HPB) [21,25]. In addition, COTL-1 was identified as an upregulated protein in SCLC by Fahrmann et al and Hye-Cheol et al [22,24]. On the contrary, HBA and HBB subunits were downregulated proteins in SCLC identified by both Pedersen et al and Sugar et al [28,30].…”
Section: Proteomic Findings In Sclc Compared With Controlsmentioning
confidence: 99%
“…At the same time, Kang et al reported an upregulation of the beta subunit (HPB) [21,25]. In addition, COTL-1 was identified as an upregulated protein in SCLC by Fahrmann et al and Hye-Cheol et al [22,24]. On the contrary, HBA and HBB subunits were downregulated proteins in SCLC identified by both Pedersen et al and Sugar et al [28,30].…”
Section: Proteomic Findings In Sclc Compared With Controlsmentioning
confidence: 99%